Hepatitis B and C viruses and sexually transmitted disease patients in Jamaica. Issue 4 (1st August 2001) - Smikle, M; Dowe, G; Hylton-Kong, T; Williams, E
Abstract : Objectives: To determine the prevalence of hepatitis C virus (HCV), hepatitis B virus (HBV), human immunodeficiency virus (HIV) infections, and risk factors for HCV and HBV infections in sexually transmitted disease (STD) clinics in Jamaica. Methods: A prospective observational cohort study was carried out. Blood was collected from 485 consecutive patients attending the comprehensive health centre in Kingston, Jamaica. Serum was tested using commercially prepared reagents and standard procedures for antibodies to HCV (anti-HCV), hepatitis B core antigen (anti-HBc), hepatitis B surface antigen (HBsAg), HIV-1 infection, and syphilitic infection. Sociodemographic and sexual characteristics of the patients were recorded for assessment as risk factors for HCV and HBV infections. Results: None of the patients had anti-HCV, 21.0% had anti-HBc, 3.2% HBsAg, 2.5% tested positive for HIV-1, and 5.2% had reactive serological test for syphilis. Age was the only independent risk factor identified for anti-HBc positivity. Conclusions: The data obtained in this study were not in support of sexual transmission of HCV or HBV infections in Jamaica. Carefully designed multicentre studies could provide more consistent information on the transmission of these viruses by sexual routes.